Penghayatan Spiritualitas Katekis oleh Mahasiswa STP-IPI Malang Program Studi Pelayanan Pastoral - Teodora Agustina Ripo Ngiso; Maria Oktaviana Lika; Klemen; Maria Grisela Gale; Emiliana Yutran Mete; Teresia Noiman Derung (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
Catechist spirituality is a profession that is engaged in and owned by a special person who dedicates himself to the education of faith in Jesus because of his professionalism in the field of Catholic education and teaching. Living the vocation to become a catechist is not a stage that is passed at a certain time, but lived for a lifetime in accordance with the vocation to become a catechist. The vocation to be a catechist can only endure, resonate, take root within if it is based on the appreciation of catechist spirituality. A catechist is a person who is specifically called to be involved in the work of proclaiming faith in Christ. The method used in this study is to use several questions as guidelines to obtain information related to the purpose of the study. In this study, researchers took respondents, namely prospective catechists or pastoral workers in the STP-IPI Malang study program from level two (2) and level (3). The purpose of this study is to see how to increase awareness of catechist spirituality of Pastoral Care Study Program Students. The result obtained in this study is that students have begun to live the catechist spirituality just not fully and are still struggling to be able to follow the educational process as prospective catechists or pastoral workers. Thus, it can be concluded that the education and formation of catechist spirituality plays an important role in improving the quality of life of prospective catechists or pastoral workers both spiritually, knowledge and skills.